The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s1806-66902011000200036
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat cuts of lambs receiving increasing levels of concentrate

Abstract: -The use of concentrate for sheep grazing Buffel grass may improve the productive performance and carcass traits of animals. The objective of present trial was to evaluate the productive performance and carcass traits of sheep grazing Buffel grass receiving different concentrate levels. The concentrate levels used were: 0; 0.33; 0.66 and 1.0% of dry matter in relation to body weight. Forty lambs were used, ten animals by treatments, with 16.5 ± 2.0 kg of initial body weight and 20.97 kg final body weight, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Increases in HCW and LM with an increasing proportion of WCS are consistent with changes in ADG and final live weight (Félix-Bernal et al, 2014;Hernández et al, 2017). The tendency of a lower dressing percentage of lambs receiving diets with a greater amount of SPR reflects the comparatively low apparent digestibility of SPR fiber, resulting in greater ruminal fill (Vinhas-Voltolini et al, 2011). The observed increase in fat thickness is consistent with greater ADG and final carcass weight (Estrada-Angulo et al, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…Increases in HCW and LM with an increasing proportion of WCS are consistent with changes in ADG and final live weight (Félix-Bernal et al, 2014;Hernández et al, 2017). The tendency of a lower dressing percentage of lambs receiving diets with a greater amount of SPR reflects the comparatively low apparent digestibility of SPR fiber, resulting in greater ruminal fill (Vinhas-Voltolini et al, 2011). The observed increase in fat thickness is consistent with greater ADG and final carcass weight (Estrada-Angulo et al, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…However, because of the protein and energy imbalance, the animal may come to accumulate fat without accumulating muscle, causing the carcass characteristics to be possibly compromised, since animals may obtain the same gain, consisting of fat accumulation only, rather than protein conversion into muscle. Voltolini et al (2011) studied the yield of commercial cuts and non-carcass components of lambs receiving increasing levels of concentrate, kept on a buffelgrass pasture, and fed a diet formulated with 20% crude protein and 75% total digestible nutrients, and observed that this diet did not affect carcass weight, but influenced the carcass yield of these animals. Silva et al (2010) evaluated the effect of supplementation on the tissue composition of commercial cuts from F1 (Boer × mixed breed) crossbred goats finished on a native pasture, receiving supplementation levels (0.0, 0.5, 1.0, and 1.5% live weight, on a dry matter basis), and slaughtered at 25.12, 26.62, 28.56, and 29.19 kg, respectively, and observed that, as the supplementation levels were increased, slaughter weight also increased.…”
Section: Discussionmentioning
confidence: 99%